PENGARUH KONTROL DIRI TERHADAP KENAKALAN REMAJA SISWA KELAS VIII DI SMP NEGERI 2 TENGARAN - Afrizal, Denis Seli; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the significance of the influence of self-control on juvenile delinquency in class VIII students at SMP Negeri 2 Tengaran. This type of research is quantitative research with a causal comparative method. The population in this study was class VIII students at SMP Negeri 2 Tengaran, totaling 292. The sample used was the Isaac and Michael table with an error rate of 5%, so the sample taken was 158. The sampling technique used in this research was simple random. sampling. The data collection technique used was the Likert scale (self-control scale and juvenile delinquency scale). The data analysis technique used is the simple linear regression analysis method. The results of the research show that there is a significant influence between self-control on juvenile delinquency in class VIII students at SMP Negeri 2 Tengaran. This is proven by the results of the F-count > F-table (14,721 > 3.90) and the significance value of 0.000 < 0.05, which means that self-control has a significant influence on juvenile delinquency. Based on these results, (H1) is accepted and Ho is rejected.